Insights Into Potato Spindle Tuber Viroid Quasi-Species From Infection to Disease - Adkar-Purushothama, Charith Raj; Bolduc, François; Bru, Pierrick; Perreault, Jean-Pierre (Frontiers in Microbiology, 2020)
Viroids are non-coding RNA plant pathogens that are characterized by their possession of a high mutation level. Although the sequence heterogeneity in viroid infected plants is well understood, shifts in viroid population dynamics due to mutations over the course of infection remain poorly understood. In this study, the ten most abundant sequence variants of potato spindle tuber viroid RG1 (PSTVd) expressed at different time intervals in PSTVd infected tomato plants were identified by high-throughput sequencing. The sequence variants, forming a quasi-species, were subjected to both the identification of the regions favoring mutations and the effect of the mutations on viroid secondary structure and viroid derived small RNAs (vd-sRNA). At week 1 of PSTVd infection, 25% of the sequence variants were similar to the “master” sequence (i.e., the sequence used for inoculation). The frequency of the master sequence within the population increased to 70% at week 2 after PSTVd infection, and then stabilized for the rest of the disease cycle (i.e., weeks 3 and 4). While some sequence variants were abundant at week 1 after PSTVd infection, they tended to decrease in frequency over time. For example, the variants with insertions at positions 253 or 254, positions that could affect the Loop E as well as the metastable hairpin I structure that has been shown important during replication and viroid infectivity, resulted in decreased frequency. Data obtained by in silico analysis of the viroid derived small RNAs (vd-sRNA) was also analyzed. A few mutants had the potential of positively affecting the viroid’s accumulation by inducing the RNA silencing of the host’s defense related genes. Variants with mutations that could negatively affect viroid abundance were also identified because their derived vd-sRNA were no longer capable of targeting any host mRNA or of changing its target sequence from a host defense gene to some other non-important host gene. Together, these findings open avenues into understanding the biological role of sequence variants, this viroid’s interaction with host components, stable and metastable structures generated by mutants during the course of infection, and the influence of sequence variants on stabilizing viroid population dynamics.